PENINGKATAN KEMAMPUAN MENULIS KALIMAT SEDERHANA MELALUI MEDIA KEPING KATA BERGAMBAR PADA SISWA TUNARUNGU DI SDLB - Suhardini Intikasari; Tumardi Tumardi; Endro Wahyuno (Universitas Negeri Malang, 2014)
The study aimed at describing (1) the use of pictorial words pieces media in improving simple sentence writing skills for the 2nd grader students with hearing impairment in SDLB Negeri Jombatan 7 Jombang, and (2) the improved simple sentence writing skills for the 2nd grade students with hearing impairment use of pictorial words pieces media in SDLB Negeri Jombatan 7, Jombang. This research used Class Action Research (CAR) method. The subjects of this research were the 2nd grade student with hearing impairment in SDLB Negeri Jombatan 7 Jombang. The data collecting technique included: observation, interview, and test of the students’ learning results. The findings showed that in the pre-action, the classical completes only reached 40% of the students’ total numbers. The finding showed that in cycle I, after the media were used, the degree of completeness increased by 60%. In cycle II, the students’ skills increased by 80% which met the completeness setting. It could be concluded that the use of pictorial words pieces could improve the students’ learning result in writing simple sentence. Tujuan dari penelitian ini mendiskripsikan penggunaan media keping kata bergambar dalam meningkatan kemampuan menulis kalimat sederhana pada siswa tunarungu dan mendeskripsikan peningkatan kemampuan menulis kalimat sederhana melalui media keping kata bergambar pada siswa tunarungu. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK). Teknik pengumpulan data yang digunakan meliputi observasi, wawancara, tes hasil belajar siswa. Penelitian ini dilakukan dalam dua siklus. Hasil penelitian menunjukkan bahwa di siklus I sudah ketuntasan meningkat sebesar 60%, namun belum mencapai 80%. Pada siklus II kemampuan siswa mengalami peningkatan 80%. Penelitian ini berhasil mencapai indikator keberkhsilan yang ditentukan.